The Influence of Foreign Investors on Firm Performance in Malaysia: A Case of Trading and Services Listed Firms - Mohd Abdullah Jusoh; Marlina Rashid; Mohd Na'eim Ajis (International Journal of Supply Chain Management, 2020)
Previous studies examining the relationship of foreign investors and form performance produced inconclusive finding. These studies assumed that a linear relation exists between foreign shareholdings and firm performances. This study examines the relationship between foreign ownership and firm performance of trading and services listed firms in Malaysia.  The research utilizes the agency theory and uses ROA and Tobin’s Q as the firm performance indicator.  Foreign shareholdings had been identified as the predictor variables and firm size and leverage are the controlled variables.  It is found that there is a significant relationship between foreign ownership with firm performance.  Apart from that, it is also found that higher concentrated foreign ownership enhances firm performance. Malaysia is uniquely suitable for a study on foreign shareholdings as Malaysia is currently embarked on an ambitious journey to transform itself into a high income economy by 2020 through the Economic Transformation Programme (ETP) by boosting both investments and private consumption